Economic Burden of Unintended Pregnancies from Societal Perspective: A Case of Nepal - Sapkota, Vishnu Prasad; Dhakal, Liladhar; Adhikari, Shiva Raj (Economic Journal of Development Issues, 2017)
Introduction: Unintended pregnancy includes unwanted and mistimed pregnancy. Nepal has high proportion of unintended pregnancies. An unintended pregnancy has cost implication through different medical conditions to individual, service provider and society. However, till date there is no information about how much cost does the unintended pregnancy incur to the society in Nepal. The objective of this study is to estimate the national annual economic burden of unintended pregnancies in Nepal.Methods: This study adopted societal perspective to identify, measure and value the resources required to manage pregnancy outcomes. The costs include direct medical costs, direct non-medical costs and indirect costs. We collected data for this study from 27 hospitals and 121 maternal service clients. Transition probabilities were taken from several secondary sources. Total annual burden of unintended pregnancy was estimated by a Markov model using the cohort simulation approach. The input parameters in the model were costs and likelihood of occurrence of the given pregnancy outcome.Findings: Total annual burden of unintended pregnancies was estimated to be 2649.558 and 12330.59 NPR from provider and societal perspective. The greatest share of the burden was borne by delivery services followed by management of maternal and ANC check-ups. The total burden is most sensitive to cost of normal delivery, CS and ANC services.Conclusion: Majority of unintended pregnancies undergo full term pregnancy incurring huge economic burden to the society. National Annual economic burden was estimated to be around 2649.558 and 12330.59 NPR from provider and societal perspective. Programs reducing unintended pregnancies will provide economic benefit to the society. Economic Journal of Development Issues Vol. 19 & 20 No. 1-2 (2015) Combined Issue, Page: 83-99